aboutsummaryrefslogtreecommitdiff
path: root/gupta/portfolio.tex
blob: 25b41b31cc51d0ba10ee4b59c956c3fe89eceacc (plain)
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
259
260
261
262
263
264
265
266
267
268
269
270
271
272
273
274
275
276
277
278
279
280
281
282
283
284
285
286
287
288
\newfam\bbold
\def\bb#1{{\fam\bbold #1}}
\font\bbten=msbm10
\font\bbsev=msbm7
\font\bbfiv=msbm5
\textfont\bbold=\bbten
\scriptfont\bbold=\bbsev
\scriptscriptfont\bbold=\bbfiv

\def\clap#1{\hbox to 0pt{\hss #1 \hss}}
\headline{\vtop{\hbox to \hsize{\strut\rlap{Math 2106 - Dr. Gupta}\hfil
\clap{\bf Portfolio}\hfil\llap{Spring 2022}}\hrule height .5pt}}

\def\section#1{\medskip\vskip0pt plus 1in\goodbreak\vskip 0pt plus -1in%
\noindent{\bf #1}}
\def\endproof{\leavevmode\hskip\parfillskip\vrule height 6pt width 6pt
depth 0pt{\parfillskip0pt\medskip}}
\def\problem#1{\medskip\vskip0pt plus 1in\goodbreak\vskip 0pt plus -1in\item{#1}}
\def\nmid{\hskip-3pt\not\hskip2.5pt\mid}

\problem{1.} Direct proof

Suppose $x,y\in\bb Z.$ If $x$ and $y$ are odd, then $xy$ is odd.
(Homework 3---Hammack 4.4)

{\bf Proof.}

Let $x,y\in\bb Z$ such that $x$ and $y$ are odd.
We will show that $xy$ is odd.
From the definition of odd we have integers $j,k\in\bb Z$ such that
$x=2j+1$ and $y=2k+1.$
$$xy = (2j+1)(2k+1) = 4jk+2j+2k+1 = 2(2jk+j+k) + 1.$$

By integer closure, $2jk+j+k\in\bb Z,$ so by the definition of odd, we
have shown that $xy$ is odd.
We have shown that the product of odd integers is odd.
\endproof

\problem{2.} Contrapositive proof

Prove that if $n^2$ is even, then $n$ is even. (Quiz 3)

{\bf Proof.}

We will show this by contraposition.
Let $n$ be an odd number (i.e. not even).
We want to show that $n^2$ is an odd number.
Since $n$ is odd, there must exist $j\in\bb Z$ such that $n=2j+1.$
$$n^2 = (2j+1)^2 = 4j^2+4j+1 = 2(2j^2+2j) + 1.$$
By integer closure, $2j^2+2j\in\bb Z,$ so we have shown that $n^2$ is
odd (i.e. not even).
We have shown that if $n^2$ is even, then $n$ is even.
\endproof

\problem{3.} Proof by contradiction

$\sqrt 6$ is irrational. (Homework 4---Hammack 6.4)

{\bf Proof.}

Assume for the sake of contradiction that $\sqrt 6$ is rational.
We then have that $\sqrt 6 = {p\over q}$ for some $p,q\in\bb Z$ s.t.
$\gcd(p,q) = 1$ (there is no $m>1$ such that $m\mid p$ and $m\mid q$).

Squaring both sides, we find
$$6 = {p^2\over q^2} \to p^2 = 6q^2 = 2(3q^2),$$ from which $3q^2\in\bb
Z$ tells us $2\mid p^2.$

{\bf Lemma.}
We will show that $2\mid p^2$ implies $2\mid p$ by contrapositive.
Let $2\nmid p,$ so $p = 2k + 1$ for some $k\in\bb Z.$
We then compute $p^2 = 4k^2 + 4k + 1 = 2(2k^2+2k) + 1,$ and
$2k^2+2k\in\bb Z,$ so $2\nmid p^2.$
\endproof

By the lemma, $2\mid p$ and $4\mid p^2,$ so there exists $k\in\bb Z$
s.t. $p^2 = 4k.$
We then get $4k = 6q^2$ and $2k = 3q^2.$ % TODO missing proof that 2k=nm.
So $q^2$ must be even, and as we've shown $2\mid q^2$ gives $2\mid q.$
Thus, $\gcd(p,q) = 2 \neq 1,$ giving a contradiction, meaning $\sqrt 6$
is irrational.
\endproof

\problem{4.} Equivalence proof

Let $A$ and $B$ be sets. Prove that $A\subseteq B$ if and only if $A\cap
B = A.$ (Homework 5---Hammack 8.22)

{\bf Proof.}

$(\Rightarrow)$

Let $A\subseteq B.$ Let $x\in A.$ By subset, $x\in B.$ And if and only
if $x\in A$ and $x\in B,$ $x\in A\cap B,$ so $A = A\cap B.$

$(\Leftarrow)$

Let $A\cap B = A.$ This implies $A\subseteq A\cap B.$
Let $x\in A.$
By subset, we know that $x\in A\cap B,$ and from that, $x\in B.$
This is the definition of $A\subseteq B.$
\endproof

\problem{5.} A proof involving sets

Let $A,$ $B,$ and $C$ be arbitrary sets. Prove that if $A-C\not\subseteq
A-B,$ then $B\not\subseteq C.$ (Homework 5 --- Problem 1)

{\bf Proof.}

We will show this by contrapositive.
Let $A$, $B,$ and $C$ be arbitrary sets such that $B\subseteq C.$
We will show that $A-C\subseteq A-B.$

$(\subseteq)$

Let $x\in A - (B\cap C).$
This gives us $x\in A$ and $x\not\in B\cap C.$
We get $x\not\in B$ or $x\not\in C.$
WLOG, let $x\not\in B.$
$x\in A$ and $x\not\in B,$ so $x\in A-B,$ so $x\in (A-B)\cup(A-C).$

$(\supseteq)$

Let $x\in (A-B)\cup (A-C).$
This gives $x\in A-B$ or $x\in A-C.$
WLOG, let $x\in A-B.$
Therefore, $x\in A$ and $x\not\in B.$
This implies $x\not\in B\cap C,$ so $x\in A-(B\cap C).$

Since we have $A-(B\cap C) \subseteq (A-B)\cup(A-C)$ and $(A-B)\cup(A-C)
\subseteq A-(B\cap C),$
we obtain $$A-(B\cap C) = (A-B)\cup(A-C).$$
\endproof

\problem{6.} An induction (or strong induction) proof

Concerning the Fibonacci sequence, prove that $\sum_{k=1}^n F_k^2 =
F_nF_{n+1}.$ (Homework 6---Hammack 10.26)

{\bf Proof.}

First, we define the Fibonacci numbers as $F_1 = F_2 = 1,$ and for
$k>2,$ $F_k = F_{k-1} + F_{k-2}.$

We will show this identity for all $n\in\bb Z,$ where $n\geq 1,$ by
induction.
For $n=1,$ $\sum_{k=1}^n F_k^2 = F_1^2 = 1 = 1\cdot 1 = F_1F_2.$

We now assume for some $j\geq 1,$
$$\sum_{k=1}^j F_k^2 = F_jF_{j+1},$$
and we will show that $\sum_{k=1}^{j+1} F_k^2 = F_{j+1}F_{j+2}$ to
complete the inductive step.
Adding $F_{j+1}^2$ to the inductive hypothesis and simplifying gives
$$\sum_{k=1}^{j+1} F_k^2 = F_jF_{j+1} + F_{j+1}F_{j+1} =
F_{j+1}(F_j+F_{j+1}) = F_{j+1}F_{j+2},$$
by definition of the Fibonacci numbers.

We have shown by induction that for all $n\in\bb Z,$ s.t. $n\geq 1,$
$$\sum_{k=1}^n F_k^2 = F_nF_{n+1}.$$
\endproof

\problem{7.} Proof a relation is an equivalence relation

Suppose $R$ and $S$ are two equivalence relations on a set $A.$ Prove
that $R\cap S$ is also an equivalence relation. (Homework 6---Hammack 11.2.10)

{\bf Proof.}

The equivalence relations $R$ and $S$ on $A$ are, by definition,
reflexive, symmetric, and transitive.
We will now show that $R\cap S$ is reflexive, symmetric, and transitive
(so it is an equivalence relation).

\smallskip
(Reflexive)

$R$ and $S$ are reflexive, so for all $a\in A,$ we know $(a,a)\in R$ and
$(a,a)\in S.$
Therefore, $(a,a)\in R\cap S,$ so $R\cap S$ is reflexive.

\smallskip
(Symmetric)

Let $(x,y)\in R\cap S.$
By symmetry, $(x,y)\in R$ implies $(y,x)\in R.$
Similarly, this implies $(y,x)\in S.$
From these, $(y,x)\in R\cap S,$ so $R\cap S$ is symmetric.

\smallskip
(Transitive)

Let $(x,y),(y,z)\in R\cap S.$ We will show $(x,z)\in R\cap S.$

$(x,y),(y,z)\in R,$ and by transitivity, $(x,z)\in R.$
Similarly, $(x,z)\in S,$ so $(x,z)\in R\cap S.$
We have shown that $R\cap S$ is transitive.

\smallskip
We have now shown that $R\cap S$ is an equivalence relation.
\endproof

\problem{8.} Injectivity or surjectivity of a function

A function $f: \bb Z\to \bb Z\times\bb Z$ is defined as $f(n) =
(2n,n+3).$ Verify whether this function is injective and whether it is
surjective (Homework 7---Hammack 12.2.4).

{\bf Proof.}
This function is injective but not surjective.

\smallskip
(Injective)

Let $m,n\in\bb Z$ such that $f(n) = f(m)$ or $(2n,n+3) = (2m,m+3).$
Then, $2n=2m,$ and rearranging, $n=m.$
This shows $f$ is injective.

\smallskip
(Surjective)

We will show there is no $n$ such that $f(n) = (0,0),$ thereby showing
$f$ is not surjective.
$(2n, n+3) = (0,0)$ implies $2n = 0$ and $n = 0,$ but $n+3 = 0+3 = 3
\neq 0,$ thereby dissatisfying the second part of the ordered pair.
$f$ is not surjective.

We have shown $f$ is injective but not surjective. \endproof

\problem{9.} A proof that something is a group

Let $S = \bb R\setminus \{-1\}$ and define a binary operation on $S$ by
$a*b = a+b+ab.$ Prove that $(S,*)$ is an abelian group. (Homework
10---Judson 3.5.7)

{\bf Proof.}

First, we show that the group operation is closed on $S.$
Clearly, if $a,b\in S,$ then $a,b\in\bb R$ and $a*b\in\bb R$ by closure
of the reals.
However, we must show that $a+b+ab \neq -1.$
For the sake of contradiction, we assume $a+b+ab=-1.$
Rearranging, $0 = a+b+ab+1 = (a+1)(b+1),$ implying $a+1=0$ or $b+1=0.$
Without loss of generality, we treat $a+1=0$ and obtain $a=-1,$ meaning
$a\not\in S,$ giving a contradiction, and showing that $*$ is closed on
$S.$

Now, we show that $(S,*)$ is abelian.
Again, let $a,b\in S.$
We compute $a*b = a+b+ab = b+a+ba = b*a,$ by commutativity of addition
and multiplication on the reals.

Next, we must show that $0$ is the identity element of $(S,*).$
With $a\in S,$
$$0*a = 0+a+0a = a,$$
and since $*$ is commutative, $a*0 = a,$ so $0$ is the identity.

Last, we must show that for all $a\in S,$ we have $a^{-1}$ such that
$a*a^{-1} = 0$ (this also implies $a^{-1}*a = 0$ by commutativity).
Let
$$a^{-1} = -{a\over 1+a} = {1\over 1+a}-1,$$
which is guaranteed to exist because $a\neq -1,$ so $1+a\neq 0.$
Also $a^{-1}\in S$ because ${1\over 1+a}\neq 0,$ so ${1\over 1+a}-1 =
a^{-1}\neq -1,$ and $a^{-1}\in\bb R$ by real closure, so $a^{-1}\in S.$

Computing the product,
$$a*a^{-1} = a-{a\over 1+a} - {a^2\over 1+a} = {a(1+a)\over 1+a} -
{a+a^2\over 1+a} = 0,$$
so $a^{-1}\in S$ exists for all $a\in S.$

\problem{10.} A proof of your own choosing

Let $a,b\in G.$ Prove that the order of $ab$ is the same as the order of
$ba$ (Homework 10---Judson 4.5.23c)

{\bf Proof.}

To show that $|ab|=|ba|,$ we will show that $(ab)^n=e$ if and only if
$(ba)^n=e.$
WLOG, we only need show that $(ba)^n=e$ if $(ab)^n=e.$

Let $(a,b)^n = e.$
$(ab)^{n+1}$ can be written as $(ab)^n ab = eab$ and as $a(ba)^nb.$
Setting these equal,
$$ab = a(ba)^nb \Rightarrow a^{-1}abb^{-1} = a^{-1}a(ba)^nbb^{-1}
\Rightarrow e = (ba)^n.$$

\bye